Low Complication Rates Associated With the Application of Lower Extremity Traction Pins. Issue 8 (August 2015) - Austin, Daniel C.; Donegan, Derek; Mehta, Samir
Abstract : Objective: To quantify the infection risks of temporary lower extremity traction pins and compare these rates to nationwide and institution-specific surgical site infection rates. Additionally, to qualitatively describe pin site infections and to analyze the impact of traction pins on infection risks at associated open reduction internal fixation (ORIF) surgical sites. Design: A retrospective case–control study. Setting: Level I Urban University Trauma Center. Patients: One hundred sixty-nine cases of traction pin application occurring in 157 unique patients extracted from a trauma patient database. Intervention: Bedside application of a traction pin in the femur or tibia. Main Outcome Measurements: Rates of 90-day and 1-year minor and major infections at pin insertion locations and at ORIF wounds associated with traction pins. Results: A single infection, a septic knee, was reported. There were no superficial infections or osteomyelitis cases observed. The 90-day and 1-year rates of infection were identical with a per pin infection rate of 0.6% [95% confidence interval (CI), 0.1%–3.4%], a minor infection rate of 0.0% (95% CI, 0.0%–2.3%), and a major infection rate of 0.6% (95% CI, 0.1%–3.4%). Observed rates were lower than, but statistically similar to, nationwide infection rates for open reduction procedures and similar to institution-specific infection rates for arthroplasty procedures. Infection rates at associated ORIF wounds were not increased in comparison with nationwide controls. Pin placement played a definitive role in the infection observed. Conclusions: Temporary lower extremity traction pins have low infection rates and can be safely placed at the bedside. Careful pin placement and review of postinsertion radiographs is necessary to avoid iatrogenic infection. Level of Evidence: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.